A new type of sample unit for the efficient assessment of diverse tree communities in complex forest landscapes - Sheil, Douglas; Ducey, M.J.; Sidiyasa, K.D.; Samsoedin, I. (2003)
The paper presents a new and versatile sample unit suitable for rapid assessments of tropical forest in heterogeneous areas. The method uses multiple applications of small and easy-to-apply variable subunits. Compared with any fixed-area approach the sample unit is quick and easy to apply even in difficult terrain, and the amount of information collected varies little with stem densities. This paper describes the method, discuss the nature of the resulting data and show how various stand characters can be calculated. The calculation of basic stand parameters from the sample data does not require any sophisticated analyses, and some worked examples are provided to ensure that the calculations are accessible. To demonstrate the statistical theory underlying this class of methods, and the good performance of the estimation methods, a more formal theoretical treatment is included as an appendix. The approach offers considerable promise for efficient forest assessments.